UPS With Half-Bridge Converter Based On Type-2 Fuzzy Logic Controller - Setiawan, David Benny; Efendi, Moh Zaenal; Eviningsih, Rachma Prilian (Electrical Engineering, Universitas Mercu Buana, 2025)
Electricity is one of the most important needs. There are many electronic devices that support and facilitate human. Electrical disturbances are an inseparable part of the existence of electrical energy and we often encounter power outages with very fast and sudden time lags. The sudden disconnection of the power source can cause various losses, one of which is damage to the electronic equipment used or the loss of important data. Losses resulting from an abrupt power source failure can be effectively managed and reduced by incorporating a UPS (Uninterruptible Power Supply) unit between the power source and electronic devices. The converter and method used in this journal is the Half-Bridge Converter with the Type 2 Fuzzy Logic Controller method which functions to control the output of the Converter to be stable. The PLN source or input will be rectified with the Rectifier and lowered by the Half-Bridge Converter which will later be used to charge the battery. The output of the Half-Bridge Converter will be controlled using the Type 2 Fuzzy Logic Controller method. When the PLN source is still there, the battery will be in a charging position, and after the PLN source is lost or extinguished, the static switch will change the load source from the PLN source to a battery source. The output from the battery will be forwarded to the inverter and directly to the load. In this journal, the results of each simulation carried out are appropriate and close to the value of the plan. From the tests that carried out with Fuzzy Type-2, the average voltage value was 13.802V with an average error value of 0.055%, which is close to the planning and the error obtained is relatively small.